Revitalization of Character Development in Civic Education Learning Management - Tjeppy Tjeppy (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to see the process of reforming education management that impacts students' character development through learning civic education to foster a sense of discipline and defend the country, so that character development is formed. This study uses a descriptive method with a qualitative approach. The data triangulation analysis is strengthened by the literature related to this research. The study results explain that civics learning management improves students' ability to understand various learning methods to be more creative and innovative. Civics lessons play a role in forming student character supported by well-organized education management, improves teachers' performance in delivering civic education subjects, and develop students' ability to instill high national values through civics education.